(x-3)(2x+3)=0

Simple and best practice solution for (x-3)(2x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(2x+3)=0 equation:


Simplifying
(x + -3)(2x + 3) = 0

Reorder the terms:
(-3 + x)(2x + 3) = 0

Reorder the terms:
(-3 + x)(3 + 2x) = 0

Multiply (-3 + x) * (3 + 2x)
(-3(3 + 2x) + x(3 + 2x)) = 0
((3 * -3 + 2x * -3) + x(3 + 2x)) = 0
((-9 + -6x) + x(3 + 2x)) = 0
(-9 + -6x + (3 * x + 2x * x)) = 0
(-9 + -6x + (3x + 2x2)) = 0

Combine like terms: -6x + 3x = -3x
(-9 + -3x + 2x2) = 0

Solving
-9 + -3x + 2x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -2x)(3 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-1.5, 3}

See similar equations:

| 5x^2=75 | | -2x-3-x=-3(-2x+7) | | 5x^2+25=100 | | 3(2x-3)=7 | | x^2+36=11 | | 2x^2+25=25 | | 2x^2-25=25 | | 2z^2+5=167 | | 15x+3y=12 | | 2x+5x+34*6/46=8 | | 2x+5xx=990 | | x^2=11 | | 2x+5-(2573)-257xxx=2 | | 2x+x^2=12 | | 2x+5-(-4)=4x | | 7-10x^2=1 | | 2x+72=0 | | 7x+7(x-60)=5180 | | x+(-12)=4 | | .5x+6=.3x | | .5+6=.3x | | 200-7x=110-2x | | 4(1+2x)+5=(x+6) | | -(5x^4-36x^2)*0.25=0 | | 10z+8z+2=12z+9z+5 | | -5x^4+36x^2=0 | | 5x^2-5x-2=0 | | x^3-12x^2+36x=0 | | 12x+108=96 | | x^2+10x+21= | | x+18+4x=-11-4x-16 | | .333x+8=x+10 |

Equations solver categories